- View SourceSee:

http://www-2.cs.cmu.edu/~andrej/objectivism/

I have not read it till its end yet, but it seems very nice.

Regards,

Shlomi Fish

----------------------------------------------------------------------

Shlomi Fish shlomif@...

Home Page: http://t2.technion.ac.il/~shlomif/

Home E-mail: shlomif@...

"Let's suppose you have a table with 2^n cups..."

"Wait a second - is n a natural number?" - View SourceOn Tue, Jul 16, 2002, Ofir Carny wrote about "RE: Become an Objectivist in Ten Easy Steps":
> (6) |- rational(y) & value(y, v) ==> v [Rational Value Theorem]

What do these step mean??? Where is this "value" expression defined?

> (7) |- egoist(x) <==> value(x, x = x) [definition of egoism]

What does (6) mean??

In particular "x=x" is always True (according to the same reasoning in

statement 3), so in (7) we actually have that x is an egoist if and only

if "the value of x is True", or something like that. What the heck does

that mean? Why write "x=x", when "x=x" is simply a tautology, always True,

and as we see later we indeed use that fact?

Sorry, but this whole "proof" looks like hogwash to me...

(but maybe I'm missing something...)

> (8) |- not(egoist(y)) ==> not(value(y, y = y)) [from (7) instantiating x = y]

I'm still waiting to hear what this "value" expression does, and how come

> (9) |- not(egoist(y)) ==> value(y, not(y = y)) [by not-propagation]

you can propegate a NOT into its second argument...

> (10)|- not(egoist(y)) ==> not(y = y) [by (9) and (6)]

Ok, so *finally* y=y is written as True. why was it necessary to write it

> (11)|- not(egoist(y)) ==> false [by (10) and (3)]

as y=y in the first place?? just to make it look more complicated??

This proof appears to me as valid as the following proof, that dogs can

fly:

(1) dog(x) <=> bark(x) & has_a_tail(x) [definition]

(2) dog(y) [hypothesis]

(3) arctan(1)=PI/4 [from math class]

(4) has_a_tail(y) [by (1) and (2)]

(5) can_fly(x) <=> altitude(x, arctan(1)=PI/4) [definition of flying]

(6) has_a_tail(y) & altitude(y, v) ==> v [Having-a-Tail Theorem]

(7) not(can_fly(y)) => not(altitude(y, arctan(1)=PI/4) [instantiating x=y]

(8) not(can_fly(y)) => altitude(y, not arctan(1)=PI/4) [not propegation]

(9) not(can_fly(y)) => not (arctan(1)=PI/4) [by (8), (6) and (4)]

(10) not(can_fly(y)) => false [by (9) and (3)]

(11) can_fly(y) [by (10) ad absurdum]

(12) dog(y) => can_fly(y) [by (2) and (11) by ==> introduction]

For those wondering how come I "proved" dogs can fly, well, it all rests

on my silly made-up definitions and theorems, like "definition of flying",

"having-a-tail theorem", and "not propegation" :)

--

Nadav Har'El | Tuesday, Jul 16 2002, 7 Av 5762

nyh@... |-----------------------------------------

Phone: +972-53-245868, ICQ 13349191 |A man is incomplete until he is married.

http://nadav.harel.org.il |After that, he is finished.